2019
DOI: 10.1136/bmjopen-2018-025874
|View full text |Cite
|
Sign up to set email alerts
|

Risk of myocardial infarction among people living with HIV: an updated systematic review and meta-analysis

Abstract: ObjectiveCardiovascular disease (CVD) is one of the leading non-AIDS-defining causes of death among HIV-positive (HIV+) individuals. However, the evidence surrounding specific components of CVD risk remains inconclusive. We conducted a systematic review and meta-analysis to synthesise the available evidence and establish the risk of myocardial infarction (MI) among HIV+ compared with uninfected individuals. We also examined MI risk within subgroups of HIV+ individuals according to exposure to combination antir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 80 publications
2
53
0
Order By: Relevance
“…A recent meta-analysis of 86 randomized clinical trials (RCTs) including 162,796 participants showed that increasing PUFAs intake reduces plasma TG levels by 15% and slightly decreases the risk of coronary heart disease mortality (relative risk (RR) = 0.90, 95% CI: 0.81, 1.00) and coronary heart disease events (RR = 0.91, 95% CI: 0.85, 0.97) [28]. This is of particular interest in HIV-positive subjects, since the infection is associated with an increased risk of myocardial infarction compared with uninfected individuals (RR = 1.73; 95% CI: 1.44, 2.08), with HAART seeming to be a significant determinant of this risk [29]. Moreover, PUFAs could also have a positive impact on diseases other than cardiovascular ones [30], so our data support their use in HIV-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 86 randomized clinical trials (RCTs) including 162,796 participants showed that increasing PUFAs intake reduces plasma TG levels by 15% and slightly decreases the risk of coronary heart disease mortality (relative risk (RR) = 0.90, 95% CI: 0.81, 1.00) and coronary heart disease events (RR = 0.91, 95% CI: 0.85, 0.97) [28]. This is of particular interest in HIV-positive subjects, since the infection is associated with an increased risk of myocardial infarction compared with uninfected individuals (RR = 1.73; 95% CI: 1.44, 2.08), with HAART seeming to be a significant determinant of this risk [29]. Moreover, PUFAs could also have a positive impact on diseases other than cardiovascular ones [30], so our data support their use in HIV-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…ECG examination is a useful screening tool for CVDs, particularly in resource limited settings. This is particularly relevant for HIV patients who are expected to live much longer but with high probability of living with CVDs in the era of combination ART (19). Previous studies revealed that prolonged Q-T interval, a precursor to fatal cardiac arrhythmias, is the most prominent ECG manifestation among HIV patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…results of three separate multivariable logistic regression analyses with adjustment of potential confounders to explore correlates of ST-T segment elevation, sinus tachycardia and any coded ECG abnormality, respectively. ST-T segment elevation was positively associated with higher baseline HIV viral load (≥ 4 log 10 copies/mL), (aOR = 2.08, 95% CI: 1 19. 3.63).…”
mentioning
confidence: 99%
“…Although not fully understood, the probable mechanism involves both chronic in ammation, CD4 cell depletion, endothelial dysfunction and atherosclerosis (22). It is undoubted that the worst lipid pro le (e.g.…”
Section: Discussionmentioning
confidence: 99%